A study of the prevalence of liver function disorders in patients with type II diabetes mellitus - صقر زينب; ربا سلمان (Latakia University Journal -Medical Sciences Series, 2023)
Background: Type 2 diabetes mellitus(T2DM) represents a disorder of glucose metabolism that characterized by hyperglycemia and insulin resistance. Liver involvement in T2DM is recognized in the form of non-alcoholic fatty liver disease(NAFLD) which can range from simple steatosis to liver cirrhosis. Objective: The aim of this study was to determine the prevalence of liver transaminase disorders in T2DM patients, and the association with glycemic control. Patients and Methods: A Descriptive Observational Cross Sectional study was conducted for the period one year (2021 –2022) at Tishreen University Hospital in Lattakia-Syria. The study included all T2DM patients older than 18 years with a duration of diagnosis disease longer than 6 months. Alanine transaminase(ALT) and Aspartate transaminase(AST) were measured for all patients with abdominal ultrasound. Results: The study included 189 patients with T2DM. Fatty liver disease was detected in 72 cases (38.1%) which was associated with elevated levels of ALT in 60 cases (83.3%) and AST in 24 cases (33.3%). Elevated levels of ALT were associated significantly with increasing body mass index BMI, fasting plasma glucose FPG, glycosylated hemoglobin HbA1c, total cholesterol TC, triglyceride TG, low-density lipoprotein LDL, and decreasing high density lipoprotein HDL(p<0.05). Elevated levels of ALT were observed more frequently in patients with fatty liver disease (76.9% versus 23.1%, p:0.0001). Elevated levels of AST were associated significantly with increasing BMI, FPG, HbA1c, TC, TG, and decreasing HDL(p<0.05). Elevated levels of AST were observed more frequently in patients with fatty liver disease (72.7% versus 27.3%, p:0.0001). Conclusion: The current study demonstrated presence of fatty liver disease in important percentage of T2DM patients, and elevated levels of ALT were observed more frequently, so that early diagnosis of diabetes and initiating of therapeutic intervention is considered essential to improve final outcome.